Isolation and identification of two extremely halophilic archaea from sebkhas in the Algerian Sahara - Khallef, Sakina; Lestini, Roxane; Myllykallio, Hannu; Houali, Karim (Cellular and Molecular Biology, 2018)
In Algeria, many salt lakes are to be found spread from southern Tunisia up to the Atlas Mountains in northern Algeria. Oum Eraneb and Ain El beida sebkhas (salt lakes), are located in the Algerian Sahara. The aim of this study was to explore the diversity of the halobacteria in this type of habitats. The physicochemical properties of these shallow saline environments were examined and compared with other hypersaline and marine ecosystems. Both sites were relatively alkaline with a pH around 8.57- 8.74 and rich in salt at 13% and 16% (w/v) salinity for Oum Eraneb and Ain El beida, respectively, with dominant ions of sodium and chloride. The microbial approach revealed the presence of two halophilic archaea, strains JCM13561 and A33T in both explored sebkhas. Growth occurred between 10 and 25% (w/v) NaCl and the isolates grow optimally at 20% (w/v) NaCl. The pH range for growth was 6 to 9.5 with an optimum at pH 7.5 for the first strain and 7 to 9.5 with an optimum pH at 8.5-9 for the second strain. On the basis of 16S rRNA gene sequence analysis, strains JCM13561 and A33T were most closely related to Halorubrum litoreum and Natronorubrum bangense (99% and 96% similarity, respectively).